The Effect of Behavioral Counseling Theory with Modeling Techniques Through Lesson Study to Improve Attention to Opposite Sex - I Kd Bgs Raka Novta Adi Putra; Ni Ketut Suarni; I Ketut Dharsana (International Conference on Technology and Educational Science)
This study aims to determine the influence of behavioral counseling theory modeling techniques through the Lesson Study method to increase attention to the opposite sex. The research population is 35 students. This research sample 15 students, with Pretest-Posttest Control Group Design. Data collection uses attention questionnaires against the opposite sex. From the results from the analysis tcount 8.275 > ttable 1.667 there are significant differences. So it can be concluded that behavioral counseling modeling techniques through effective lesson study to increase attention to the opposite sex. Based on the results of the analysis and discussion above, it can be stated that the proposed hypothesis is accepted based on the significance level of 5%. The conclusions in this study are the Effect of Behavioral Counseling Theory by Modeling Through Lesson Study to Increase the attention of the opposite sex.